2007
DOI: 10.21273/hortsci.42.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Affects Quality Parameters of ‘SeaDwarf’ Seashore Paspalum

Abstract: Irrigating salt-tolerant grasses with nonpotable water, like salt water, conserves fresh water resources. Advertising suggests that ‘SeaDwarf’ seashore paspalum (Paspalum vaginatum O. Swartz) is salt-tolerant and that it resists the effects of salinity on growth typically observed when irrigating other turf types with salty water. As a result, it is now being used on golf courses and home lawns in an effort to help conserve fresh water. Commensurate with the use of nonpotable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
3
5
0
Order By: Relevance
“…Among all cultivars studied, seashore paspalum exhibited the best visual quality during all three growing seasons, while saltgrass had the lowest quality (Table 6). Our findings support those of Duncan and Carrow (2000), Berndt (2007), and Lee et al (2005) who reported a high salinity tolerance in seashore paspalum and consequently a high turf quality in saline soils. Low quality ratings for inland saltgrass could not be attributed to salt stress, as water quality had no effect on turf performance in our study (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Among all cultivars studied, seashore paspalum exhibited the best visual quality during all three growing seasons, while saltgrass had the lowest quality (Table 6). Our findings support those of Duncan and Carrow (2000), Berndt (2007), and Lee et al (2005) who reported a high salinity tolerance in seashore paspalum and consequently a high turf quality in saline soils. Low quality ratings for inland saltgrass could not be attributed to salt stress, as water quality had no effect on turf performance in our study (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…However, a chemical analysis of the water used in this study (Table ) did not reveal any significant levels of constituents that might explain the increased growth or quality. Overall, salinity levels measured throughout the course of our experiment are within the genetic tolerance levels of the grasses investigated and should have no impact on their quality (Berndt, ). More research is needed to investigate why saline groundwater resulted in higher turf quality than the potable water.…”
Section: Resultsmentioning
confidence: 90%
“…Water quality did not affect green‐up of turfgrasses. Soil test results (Table ) showed that EC and SAR in March and June never reached levels that are considered detrimental for seashore paspalum or bermudagrass (Berndt, ). These results were similar to findings of Sevostianova et al.…”
Section: Resultsmentioning
confidence: 99%
“…This species can grow in high salt water concentrations and waterlogged environments, and can be used for bioremediation of contaminated (e.g., heavy metals and organic chemicals) or unproductive soils (Wang et al, 2006) and for forage production (Lee et al, 2008). In recent years, seashore paspalum has been used as a turfgrass on golf courses and other sports fields (Berndt, 2007). Some ecotypes display a wide range of tolerance to salt, drought, flooding, nitrogen level, soil conditions, soil pH, low mowing height, and extreme temperatures (Trenholm et al, 2000) which are desirable qualities for turfgrass.…”
mentioning
confidence: 99%